2021
DOI: 10.1002/bsl.2510
|View full text |Cite
|
Sign up to set email alerts
|

A heuristic study of the similarities and differences in offender characteristics across potential and successful serial sexual homicide offenders

Abstract: This heuristic study examined potential serial sexual homicide offenders (SSHOs), an unacknowledged offender group comprised of aspiring and probable SSHOs, and compared them with successful SSHOs. Data were collected on six aspiring SSHOs who each failed a single homicide attempt, 16 probable SSHOs who committed 17 homicides in separate events, and 13 successful SSHOs who killed 90 victims in separate events. The study results indicate that while potential SSHOs share more in common with successful SSHOs than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…In short, new research supports the three-victim minimum favored by Skrapec [2], the time dimension proposed by Adjorlolo and Chan [1], and the killing as motivated by personal enjoyment (as leisure experience) outlined in both reviews [1,2]. Furthermore, although aspiring or hopeful serial homicide offenders [11] appear to be distinct from actual serial homicide offenders [9,10], there remains much that researchers and professionals can continue to learn from this group. To conclude, it is strongly recommended that, based on new research, experts follow the conceptualization refined most recently by Adjorlolo and Chan [1], but with an updated three-victim (fatal) threshold rather than two.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In short, new research supports the three-victim minimum favored by Skrapec [2], the time dimension proposed by Adjorlolo and Chan [1], and the killing as motivated by personal enjoyment (as leisure experience) outlined in both reviews [1,2]. Furthermore, although aspiring or hopeful serial homicide offenders [11] appear to be distinct from actual serial homicide offenders [9,10], there remains much that researchers and professionals can continue to learn from this group. To conclude, it is strongly recommended that, based on new research, experts follow the conceptualization refined most recently by Adjorlolo and Chan [1], but with an updated three-victim (fatal) threshold rather than two.…”
Section: Discussionmentioning
confidence: 89%
“…A similar study of both male and female serial homicide offenders (N = 1258) found that two-victim offenders differed from their more prolific counterparts on important variables related to victim demographics (sex and race) and prevalence of rape at or near the time of murder [10]. These two large empirical studies found clear differences between serial homicide offenders (minimum of three victims) from serial homicide offenders with two victims but perhaps a similar psychological mindset [11]. Together, these studies clearly call for a three-victim minimum threshold, rather than two.…”
Section: Empirical Research On Minimum Victim Thresholdmentioning
confidence: 88%
“…However, despite the significant advances made by crime scientists in the West in this area, we must remember the dependence between the predictive value of the ML algorithms used and the quality of the data used therein. At present, this aspect of crime science leads to extensive discussions in the foreign academic environment [Slobogin C., 2021: [37][38][39][40][41][42][43][44][45]. This demands a balanced approach that does not allow for excesses and truly "automatic" solutions based on blind adherence to mathematical calculations [Dressel J., Farid H., 2018: 5580].…”
Section: Problems Of Tomorrowmentioning
confidence: 99%
“…Yaksic et al. (2021) reported on 22 potential serial sexual murderers of varied ages who failed to reach their goal of becoming full‐fledged serial murderers between 2013 and 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Yaksic (2022) found that there were 381 serial murderers who were apprehended in the 10-year period between 2011 and 2021 or approximately 38 offenders annually. Yaksic et al (2021) reported on 22 potential serial sexual murderers of varied ages who failed to reach their goal of becoming full-fledged serial murderers between 2013 and 2018. However, there is still only scant research on serial sexual murder by children and their annual prevalence is unknown.…”
Section: Introductionmentioning
confidence: 99%